THE EFFECT OF LEARNING INTEREST ON LITERACY AND NUMERACY LEVELS - Sabar Riyanto, dkk. (YAYASAN CENDEKIA CITRA GEMILANG, 2024)
This study aims to determine the effect of interest in learning on the level of literacy and numeracy of grade V students in Cluster III, Pituruh Purworejo. The type of research used in this study is quantitative research using the ex post facto method. The subjects in this study were all fifth-grade students of SD Negeri Sutogaten, SD Negeri Kaligintung 2, SD Negeri Kaligintung 1, and SD Negeri Kaligondang in the 2023/2024 academic year with a total of 65 students. Data collection techniques in this study used scales and tests. The research data are the scale score of students' interests in learning and the literacy and numeracy test results of students. Data analysis used in this research is descriptive statistical analysis and inferential statistical analysis. Descriptive statistical analysis of data includes calculating the range, number of classes, interval class length, average, and standard deviation. Inferential statistical analysis includes prerequisite testing in the form of a data normality test, linearity test, heteroscedasticity test, and autocorrelation test, then continues with hypothesis testing using a simple linear regression test. The result of this study is that there is an effect of interest in learning on literacy and numeracy of grade V students in Cluster III Pituruh Purworejo District with a significance value (2-tailed) of 0.02 <0.05. Furthermore, the R Square value of 0.081 states the effect of interest in learning on the literacy and numeracy of students.